2015
DOI: 10.1159/000369120
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Muscle Activity during Nasal High-Frequency Oscillatory Ventilation in Nonsedated Newborn Lambs

Abstract: Background: We have previously shown that nasal pressure support ventilation (nPSV) can lead to an active inspiratory laryngeal narrowing in lambs. This, in turn, can limit lung ventilation and divert air into the digestive system, with potentially deleterious consequences. On the other hand, nasal high-frequency oscillatory ventilation (nHFOV) is particularly attractive in newborns, especially since, unlike nPSV, it does not require synchronization with the patient's inspiratory efforts. Objectives: The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
(57 reference statements)
1
26
0
2
Order By: Relevance
“…Thus, patient-ventilator interaction could be better during NHFOV than with conventional NIV. However, the same study showed suppression of central respiratory drive when nasal-mask-delivered NHFOV was applied at 4 Hz 23. This effect was not mediated by hypocarbia and could be linked to several phenomena, such as an increase in vagal pulmonary stretch receptor activity24 or thoracic wall afferent activity 25.…”
Section: Physiology Of Nhfovmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, patient-ventilator interaction could be better during NHFOV than with conventional NIV. However, the same study showed suppression of central respiratory drive when nasal-mask-delivered NHFOV was applied at 4 Hz 23. This effect was not mediated by hypocarbia and could be linked to several phenomena, such as an increase in vagal pulmonary stretch receptor activity24 or thoracic wall afferent activity 25.…”
Section: Physiology Of Nhfovmentioning
confidence: 81%
“…This is an advantage given the difficulties in achieving good synchronisation during neonatal NIV and because a poor patient-ventilator interaction may significantly decrease ventilation efficiency 22. Interestingly, an animal study showed that, in contrast to non-invasive pressure support ventilation, NHFOV did not induce phasic inspiratory glottal constriction and conversely did not decrease inspiratory glottal dilatation 23. Thus, patient-ventilator interaction could be better during NHFOV than with conventional NIV.…”
Section: Physiology Of Nhfovmentioning
confidence: 99%
“…During normal spontaneous breathing, laryngeal muscles act in synchrony to open the upper airway during inspiration, decreasing resistance and easing the flow of gas through the glottis [33]. Recent studies have demonstrated that normal muscle activity during inspiration is markedly altered with the application of pressure-supported NIPPV (Table 4) [3335]. NIPPV induces an increase in inspiratory constrictor (thryoarytenoid) muscle activity while suppressing normal inspiratory dilator (cricothyroid) muscle activity, with these effects augmented as NIPPV support is increased [3335].…”
Section: Clinical Studies: Animalmentioning
confidence: 99%
“…Recent studies have demonstrated that normal muscle activity during inspiration is markedly altered with the application of pressure-supported NIPPV (Table 4) [3335]. NIPPV induces an increase in inspiratory constrictor (thryoarytenoid) muscle activity while suppressing normal inspiratory dilator (cricothyroid) muscle activity, with these effects augmented as NIPPV support is increased [3335]. Contrary to the effect of NIPPV, the application of HFNV was shown not to increase inspiratory constrictor muscle activity while maintaining normal dilator muscle activity [35] (Table 4).…”
Section: Clinical Studies: Animalmentioning
confidence: 99%
See 1 more Smart Citation